Behaviour of molecular weight distribution for the liquid fraction of pig slurry treated by anaerobic digestion - Rodríguez, D C (Environmental technology, 2011)
Pig slurry was treated in an upflow anaerobic sludge blanket (UASB) reactor. To maintain a stable operation, the organic loading rate (OLR) applied to the system was increased stepwise by decreasing the dilution ratio of the pig slurry. Finally, during the last operational stage, no dilution was applied to the influent. The reactor maintained a soluble chemical oxygen demand (CODs) removal efficiency of 82% when OLRs lower than 1.73 g CODs l(-1) d(-1) were applied, although its efficiency fell to 55% when operated at 2.48 g CODs l(-1) d(-1). System performance was not affected by the presence of free ammonia (concentrations up to 375 mg NH3 l(-1)). The distribution of the different molecular weight fractions changed significantly during anaerobic digestion. Proteins contained in the fractions higher than 10,000 Daltons are less degraded than those belonging to the lower fractions. An important percentage of both COD and BOD5 in the effluent were observed in the lowest fraction, probably caused by the presence of volatile fatty acids (VFA)